Computer-guided binding mode identification and affinity improvement of an LRR protein binder without structure determination - Choi, Yoonjoo; Jeong, Sukyo; Choi, Jung-Min; Ndong, Christian; Griswold, Karl E.; Bailey-Kellogg, Chris; Kim, Hak-Sung (PLOS Computational Biology, 2020)
Author summary It is quite challenging for computational methods to determine how proteins interact and to design mutations to alter their binding affinity and specificity. Despite recent advances in computational methods, however, in silico evaluation of binding energies has proven to be extremely difficult. We show that, in the case of protein-protein interactions where only small structural changes occur upon target binding, an integrated computational and experimental approach can identify a binding mode and drive reengineering efforts to improve binding affinity or specificity. Using as a model system a leucine-rich repeat (LRR) protein binder that recognizes human IgG1, our approach yielded a model of the protein complex that was very similar to the subsequently experimentally determined co-crystal structure, and enabled design of variants with significantly improved IgG1 binding affinity and with the ability to recognize IgG1 from other species.